Answer:
Step-by-step explanation:
(x² + 6x + 9)(x)= x²*x + 6x*x + 9*x = x³ + 6x² + 9x
Answer:
1) a <u><</u> -8 or a <u>></u> 8
2) n = -18 or n = 18
3) z = - 1/2 or z = 1/2
Step-by-step explanation:
You know that -3 is the Y intercept(vertical graph line) and then continue 2/1 every x value that is plugged in.
Answer:
a=6
Step-by-step explanation:
-6(2+(6)=-48
-6(2+6)=-48
(-6X2)+(-6+6)=-48
(-12)+(-36)=-48
-48=-48
They are equal. Tell me if I made a mistake. Thanks!
Answer:
$665.36
Step-by-step explanation:
2^16 or...
2x2x2x2x2x2x2x2x2x2x2x2x2x2x2x2 = 66536 pennies